2012
DOI: 10.1016/j.ijscr.2012.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyoma of kidney: An Indian experience with literature review

Abstract: Considering the difficulty of clinical diagnosis of this tumour, strong suspicion is indicated when a patient presents with voluminous, well circumscribed renal lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
1
7
1
Order By: Relevance
“…Although the vast majority of kidney leiomyoma cases reported in the literature are adults, they may also be detected in childhood. Leiomyomas are two times more common in women than men, and the incidence increases after the fourth decade of life (3,5). In our series, leiomyoma was detected equally in both men and women.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Although the vast majority of kidney leiomyoma cases reported in the literature are adults, they may also be detected in childhood. Leiomyomas are two times more common in women than men, and the incidence increases after the fourth decade of life (3,5). In our series, leiomyoma was detected equally in both men and women.…”
Section: Discussionsupporting
confidence: 41%
“…The patient was followed-up for 14 months and, serum creatinine and eGFR levels were 1.12 mg/dL and 44 mL/min/1.73 m 2 , respectively. genitourinary tract organs including smooth muscle cells, such as ureter, bladder, urethra, prostate, seminal vesicles, testicles, penis and scrotum (5). Renal leiomyomas are extremely rare benign tumors of the kidney with a prevalence of up to 5%, based on incidental findings of autopsy series.…”
Section: Casementioning
confidence: 99%
“…21 The quantitative analysis in this case showed that the mass was hypervascular in relation to the native kidney parenchyma and hypovascular in relation to the kidney graft. Given that guidelines from urologic associations always include CT evaluation of renal masses, we compare CEUS features with those of CT. Based on data reported in the literature, it is well known that enhancement of renal tumors has a different pattern according to renal function: RCCs are characteristically well vascularized in comparison with the renal parenchymal vascular sclerosis in chronic kidney disease, 22 and leiomyomas in patients with normal kidney function are less vascularized than the renal parenchyma, 23,24 quite the opposite pattern from that observed in this case using CEUS.…”
Section: Ceus Was Useful For Diagnosis and Evaluation Of The Renal Macontrasting
confidence: 50%
“…Renal leiomyoma could occur in capsular, parenchyma, or pelvis locations [ 20 ]. On images, renal leiomyomas usually present as solid tumors, although they could have cystic degeneration as well [ 20 ]. Renal leiomyomas are more common in women [ 20 ].…”
Section: Key Diagnostic Featuresmentioning
confidence: 99%
“…On images, renal leiomyomas usually present as solid tumors, although they could have cystic degeneration as well [ 20 ]. Renal leiomyomas are more common in women [ 20 ]. On computed tomography, renal leiomyomas are usually well defi ned and homogeneously enhanced less than normal parenchyma.…”
Section: Key Diagnostic Featuresmentioning
confidence: 99%